Regulators of the breast tumor immune microenvironment: PD-L1 and regulatory T cells - Romero, Yeni (Kansas State University, 2020)
Tumors consist of a diverse population of cancer cells as well as various tumor-infiltrating immune cells, soluble factors, and extracellular matrix proteins, which are collectively known as the tumor immune microenvironment (TIME). The interactions between cancer cells and their microenvironment heavily influence tumor progression and therapeutic responses, often leading to tumor immune evasion and therapeutic resistance. Understanding these complex interactions will help develop novel strategies to target tumor cells or improve the efficacy of existing therapies. The goal of my research was to explore the role of two regulators of the tumor immune microenvironment, PD-L1 and regulatory T cells, in triple negative breast cancer (TNBC). Programmed death-ligand 1 (PD-L1) is a negative regulator of the immune system that acts as a “brake” to keep the body’s immune responses under control. However, in cancer, PD-L1 expression leads to immune evasion and poor disease outcomes. In breast cancer, PD-L1 expression is most upregulated in the TNBC subtype. Under certain circumstances, transmembrane PD-L1 can be cleaved, generating a soluble form containing an intact receptor-binding domain. In my research, I investigated the cleavage of PD-L1 expressed on the surface of tumor cells. I found that a ~37-kDa N-terminal cleavage product of PD-L1 is released to the culture media. Analysis of the ~18-kDa C-terminal PD-L1 fragment demonstrated that this fragment is unstable and readily eliminated by lysosomal degradation. Furthermore, I identified ADAM10 and ADAM17, two members of the cell surface family of ADAM metalloproteases, as mediators of the cleavage of transmembrane PD-L1. Regulatory T cells (Tregs) are a subset of T cells that play a role in regulating or suppressing other immune cells. Tregs regulate the immune response to self and foreign antigens and help prevent autoimmune diseases by maintaining immune homeostasis. In cancer, Tregs are involved in tumor development and progression by inhibiting effector cells and reducing anti-tumor immunity. In TNBC, infiltration of Tregs into the TIME is often associated with resistance to anti-PD-L1 therapy and poor patient survival. Therefore, a better understanding of the mechanisms regulating the numbers of Tregs in the TIME of TNBC is necessary to tackle the problem of immunotherapy resistance. Claudin-low breast tumors are known to have increased numbers of tumor-infiltrating lymphocytes, specifically Tregs, as well as upregulated expression levels of ADAM12, an active ADAM metalloprotease. My goal was to investigate the role of ADAM12 in T cell accumulation to the tumor microenvironment in vivo using a mouse transplantation model of claudin-low breast cancer. Specifically, I investigated the accumulation of Tregs and other T cell subsets to tumors with or without expression of ADAM12. I found that the frequency of Tregs in tumor immune infiltrates was increased in tumors that lacked ADAM12 expression. Collectively, these findings give insight into the complex regulatory roles that PD-L1 and Tregs play in the breast cancer TIME.
Keywords: Breast cancer; Tumor immune microenvironment; Regulatory T cells; Programmed death-ligand 1; A disintegrin and metalloprotease